From anger to solidarity: The emotional echo-chamber of Gezi park protests - Erhart, Itır (Elsevier B.V., 2019)
By using the Gezi Park protests that took place in Turkey in 2013 as a case, we explore the significance of emotional echo-chamber involved in protests. The analyses are composed of thirty-seven interviews conducted with activists on how they define and understand their preferences and motivations for protesting. We discuss how participants get influenced by beliefs, motives and opinions and bring forth the changes of emotions during such processes and help create an emotional echo-chamber.
Keywords: Anger; Emotional-echo chambers; Emotions; Hope; Protest movement; Social movements; Solidarity